2018
DOI: 10.5935/abc.20180077
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention in Chronic Total Occlusion

Abstract: Percutaneous coronary intervention in chronic total occlusion is a rapidly evolving area, being considered the last frontier of interventional cardiology. In recent years, the development of new techniques and equipment, as well as the training of specialized personnel, increased their success rates, making it the most predictable procedure available. Although the number of randomized and controlled studies is still limited, results from large multicentered registries allow us to safely offer this intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 65 publications
0
12
0
1
Order By: Relevance
“…The present analysis is relevant because equipment and resources are generally more limited in Latin America, mainly due to financial restraints and fragmented regulatory issues 25 . Registry data from very experienced CTO centers report success rates of approximately 90%, higher than found in our report.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The present analysis is relevant because equipment and resources are generally more limited in Latin America, mainly due to financial restraints and fragmented regulatory issues 25 . Registry data from very experienced CTO centers report success rates of approximately 90%, higher than found in our report.…”
Section: Discussionmentioning
confidence: 51%
“…As mentioned above, our lower success rates could be related to more limited resources and because many centers and operators are in different phases of the learning curve for CTO PCI 25 . This is exemplified by the variability of success rates and number of patients included amongst participating centers and countries in this report.…”
Section: Discussionmentioning
confidence: 84%
“…Planning of the recanalization procedure requires the use of angiographic scores to estimate the probable success rate and the type of approach. 8 The J-CTO score is the most widespread and oldest one.15 Higher J-CTO score significantly indicates lower success rates, greater use of contrast, more frequent use of retrograde approach and longer procedures. 13,14 In the present study, we aimed to investigate the association of J score with percutaneous revascularization success in chronic coronary total occlusion patients.…”
Section: Discussionmentioning
confidence: 99%
“…Occlusions with the minimal passage of contrast without opacification of the distal vessel are considered "functional CTO." 8 CTOs occur in 18-52% of individuals submitted to coronary angiography and who have coronary heart disease. 9 Recent reviews showed a prevalence between 16 and 20%.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of CTO-PCI technology and the wide application of coronary stents, the problem of in-stent restenosis is gradually exposed. The in-stent restenosis after CTO-PCI with bare mental stents was as high as 50%, which undoubtedly hindered its application in this situation (7). The first-generation drug-eluting stent (DES) was introduced to solve in-stent restenosis in 2002, and its anti-proliferative drugs can inhibit the proliferation of vascular endothelial cells and eliminate neointimal hyperplasia, the incidence of instent restenosis after CTO-PCI was reduced to 7-8.2% (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%